EVALUATION OF TREATMENT OUTCOMES OF VESTIBULAR MIGRAINE PATIENTS - Abolfazl Atalu; Firouz Amani; Aran Nikpay (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Currently there are several treatment plans for prophylaxis of vestibular migraine, but these treatments are based on physician's observations and there have not been studied on a consensual treatment plan. Objective: Based on diagnostic criteria, we collected vestibular migraine patients and created an individualized treatment plan for 3 months to interpret treatment results. Methods: In this prospective cross-sectional study, 28 patients with headache and dizziness diagnosed for vestibular migraine were enrolled. Demographics, clinical picture, and treatment results were evaluated for all patients at baseline and after three months follow-up duration. Collected data analyzed by statistical methods in SPSS. Results: Due to results, all of the patients with vestibular migraine were female and mostly were in the 30 to 50 years old age group. Dizziness, Headache before vestibular symptoms, increased intensity of headache on excretion, intermediate to high migraine intensity, and throbbing pain were the most common symptoms in the patients. The most common drugs used in the treatment were somatriptan, topiramate and Magnesium+Vitamin B6. After 3 months of treatment, duration, intensity, and frequency of migraine and frequency of dizziness episodes were significantly decreased but there was not a significant relationship between treatment plan and dizziness episodes in terms of duration and intensity. Conclusion: Effectiveness of the drugs in decreasing dizziness episodes can be explained by the effect of the drugs in preventing migraine episodes, whereas in recent studies non-pharmocologic treatments have had a significant effect on decreasing dizziness intensity and duration. Using both pharmacologic and non-pharmocologic methods in combination, is recommended for the treatment of the vestibular migraine.